Pests and damage on corn fertilized with soil remineralizer - Rodrigues, Paula de Fátima Martins; Araújo, Dayane Aparecida de Oliveira; Almeida, Samuel Mendes; Rodrigues, Pedro Guilherme Martins; Brito, Eliane Souza Gomes; Rodrigues, Tatiana Tozzi Martins Souza (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The objective of this study was to evaluate the incidence of pests in maize fertilized with soil remineralizer from silicate rock compared to chemical fertilization with NPK. The experiment was conducted in an experimental area at the Federal Institute of Northern Minas Gerais, Campus Januária, Minas Gerais, with the cultivation of medium - cycle corwith corn grain medium-cycle in a randomized block design, with six treatments, four replications, four planting / plot lines . The treatments consisted in the supply of 0, 2, 4, 8, 16 t ha-1 remineralizer (NaturalPlus® rock powder from Ipirá, Bahia) and NPK in planting line. Twenty plants of the area of each plot were monitored weekly for pest incidence during the phenological stages V1 to V12. In the reproductive stage R3 the damage caused by the caterpillar in leaves was evaluated by means of scale of visual damage. During the survey, the occurrence of Spodoptera frugiperda, Dalbulus maidis and Diabrotica speciosa was observed in a smaller quantity in the treatments with soil remineralizer, regardless of the dose. The damage caused by the caterpillar on leaf area reduction was directly proportional to the number of caterpillars. The silicate rock remineralizer reduced the incidence of sucking insects and damage caused by caterpillars in corn.